The Efficacy of Bisphosphonates in Preventing Aromatase Inhibitor Induced Bone Loss for Postmenopausal Women with Early Breast Cancer: A Systematic Review and Meta-Analysis - Anagha, Pooleriveetil Padikkal (Hindawi Publishing Corporation, 2014)
Objectives. We aim to determine the efficacy of bisphosphonates in preventing aromatase inhibitor induced bone loss (AIBL) in postmenopausal women with early breast cancer. The secondary objective was to determine the safety of bisphosphonates. Materials and Methods. We searched electronic databases in a time period of 1995 January to 2013 June. Random effects meta-analytical models were used; between study heterogeneity and publication bias was assessed. Results. A total of six eligible studies reported the BMD T score of LS at 12 months and from that 3 trials of Zoledronic acid compared the change in BMD in immediate ZOL versus delayed ZOL done with subgroups like patients with normal BMD at baseline (OR = 5.402, 95% CI = 1.329–21.959, P value = 0.018) and osteopenic BMD at baseline (OR = 4.008, 95% CI = 2.249–7.143, P value = 0.0002). Both had a significant decrease in BMD that favoured the delayed ZOL; 3 trials of risedronate and ibandronate also had a significant decrease in BMD in AIs alone group. Immediate ZOL versus delayed ZOL also showed increased risk of getting an ADR in immediate group. Conclusion. Third generation bisphosphonates has an effect on BMD of patients who are on treatment of AIs in breast cancer. Furthermore, the patients treated with immediate ZOL had a significantly high risk of musculoskeletal ADR's than patients with delayed ZOL.